Third person effects in interview responses on life satisfaction - Adrian Chadi (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2013)
This paper investigates the finding that reported life satisfaction scores are significantly higher in the German Socio-Economic Panel when a third person is present during the interview. Even after controlling a variety of relevant factors, third person presence makes up a significant difference in satisfaction levels. A plausible explanation is that interviewees distort their responses in a favourable way. The evidence suggests that this apparently minor aspect could even affect empirical outcomes in happiness research. This study contributes to the literature in this field, especially with respect to the recently revived debate on survey methodology in the reporting of satisfaction.
Keywords: C8; D6; I3; 330; Well-being; Survey design; Interview-specific factor; Third persons; Response bias